The Mitochondrial Chaperone TRAP1 as a Candidate Target of Oncotherapy - Xie, Shulan; Wang, Xuanwei; Gan, Shuyuan; Tang, Xiaodong; Kang, Xianhui; Zhu, Shengmei (Frontiers in Oncology, 2021)
Tumor necrosis factor receptor-associated protein 1 (TRAP1), a member of the heat shock protein 90 (Hsp90) chaperone family, protects cells against oxidative stress and maintains mitochondrial integrity. To date, numerous studies have focused on understanding the relationship between aberrant TRAP1 expression and tumorigenesis. Mitochondrial TRAP1 is a key regulatory factor involved in metabolic reprogramming in tumor cells that favors the metabolic switch of tumor cells toward the Warburg phenotype. In addition, TRAP1 is involved in dual regulation of the mitochondrial apoptotic pathway and exerts an antiapoptotic effect on tumor cells. Furthermore, TRAP1 is involved in many cellular pathways by disrupting the cell cycle, increasing cell motility, and promoting tumor cell invasion and metastasis. Thus, TRAP1 is a very important therapeutic target, and treatment with TRAP1 inhibitors combined with chemotherapeutic agents may become a new therapeutic strategy for cancer. This review discusses the molecular mechanisms by which TRAP1 regulates tumor progression, considers its role in apoptosis, and summarizes recent advances in the development of selective, targeted TRAP1 and Hsp90 inhibitors.